Hubungan Antara Efikasi Diri Dengan Minat Berwirausaha Pada Difabel - Permana, Bhenny Satya Indra; , Drs. Mohammad Amir, M.Si, Psi (2016)
God has given difables the same right as the normal people to live on earth. As a matter of fact, the invalids experience the normal process of growth and development as well as the normal children do. Yet, those handicap are often underestimates, some people think they cannot work for money, they are uneducated and slow learners. They always need help as they are not independent. They can't even use the means of transportation. The worst thing, however, is that people often think that disables are suffering very bad disabilities. We can't avoid the fact that Indonesia are still facing problem related to the sufficiency of jobs, especially those which fit for the disables. The goal of this research is to find out how self efficacy relates to the interest of entrepreneurship. The hypothesis being used here is the positive relationship between self efficacy and the interest of entrepreneurship. There are at least 60 subjects being studied in this research out of all difables at BBRBD Prof. Dr. Soeharso Surakarta. The research uses quantitative method in which the self efficacy is the independent variable, while the interest of entrepreneurship is the dependent variable. Finally we have come up with the conclusion showing that there is significantly positive relation between the self efficacy and interest of entrepreneurship. The higher self efficacy leads to higher interest of entrepreneurship and vice versa. It is shown by r = 0,741 and sig. = 0,000 (p 0,001). We can see that the self efficacy is very high as well as the level of interest of entrepreneurship is. They are proven by the empiric average reaching as much as 102,95 while the hypotetic average is as much as 72,5 and the Effective Input of SE variables reaches up to 54,9%. We can conclude that there are other variables as much as 45,1% that potentially affects the social competency besides the self efficacy variables.